The Role of Exercise on Sarcopenia - GWPD, Fonseca; Souza, Francis Ribeiro de; Santos, Marcelo Rodrigues dos; Alves, Maria Janieire de Nazaré Nunes (Cardiology and Cardiovascular Medicine, 2020)
The skeletal muscle is a highly adaptable tissue and orchestrates many responses related to a healthy status. Sarcopenia, the age-related decline in muscle mass, muscle strength, and physical performance, has shown to affect up to 36.5% of adults aged ≥60 years. Currently, muscle strength has been considered as the primary indicator of sarcopenia. In this context, resistance training and its modalities have shown to improve the parameters of sarcopenia with positive impact on reducing the incidence of falls and fractures. The outcomes of resistance training are mediated primarily by an inversely proportional relationship between intensity and volume. Muscle strength gains seem to be more pronounced with higher intensity, whereas volume may be more effective in promoting muscle mass accrual. However, muscle strength improvement must increase physical performance to reflect significant clinical outcomes and adding exercise related to activities of daily living and aerobic training can be important tools in this process. In addition, resistance training associated with nutrition interventions can have additional effect on muscle mass accrual. In conclusion, adherence and safety of exercise training are important to the success of an exercise training program and depends on instruction by qualified professionals such as personal trainers and exercise physiologists.